2017
DOI: 10.1016/j.neurobiolaging.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Klotho regulates postnatal neurogenesis and protects against age-related spatial memory loss

Abstract: Although the absence of the age-regulating klotho protein causes klotho-deficient mice to rapidly develop cognitive impairment and increasing klotho enhances hippocampal-dependent memory, the cellular effects of klotho that mediate hippocampal-dependent memory function are unknown. Here we show premature aging of the klotho-deficient hippocampal neurogenic niche as evidenced by reduced numbers of neural stem cells, decreased proliferation, and impaired maturation of immature neurons. Klotho-deficient neurosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 92 publications
(161 reference statements)
3
64
0
2
Order By: Relevance
“…Collectively, the data support the possibility that αKL serum level increases can improve hippocampal plasticity and could thereby impact cognition and hippocampal function in aged persons. This effect of αKL on HC VOL is in line with findings that Klotho is an important factor for the maturation of hippocampal neurons with impact on hippocampal-dependent spatial memory function (Laszczyk et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Collectively, the data support the possibility that αKL serum level increases can improve hippocampal plasticity and could thereby impact cognition and hippocampal function in aged persons. This effect of αKL on HC VOL is in line with findings that Klotho is an important factor for the maturation of hippocampal neurons with impact on hippocampal-dependent spatial memory function (Laszczyk et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Since elevating Klotho serum levels in mice enhances cognition (Dubal et al, 2014(Dubal et al, , 2015Leon et al, 2017), strategies that increase Klotho activity or simulate its function may therefore improve cognition at different life stages and, possibly, even under pathological circumstances. Recent evidence suggests that Klotho is a regulator of postnatal neurogenesis, affecting neural stem cell proliferation and maturation sufficient to impact hippocampal-dependent spatial memory function (Laszczyk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The brain’s white matter tracts, containing neuronal axons, their associated myelin sheaths, and myelin maintaining oligodendrocytes, are particularly prominent sites for downregulation of KL with age [ 12, 13 ]. The volume of the major hippocampal output white matter tract, the fimbria, is dramatically decreased over KL-deficient mouse lifespan and this correlates with fewer oligodendrocytes [ 56–58 ]. Axon analysis across CNS white matter tracts of KL-deficient mice show impaired myelination [ 57 ].…”
Section: Oligodendrocytes and Myelinmentioning
confidence: 99%
“…The initial increase in volume may relate to dendritic arborisation (Giedd 2004 ), while the subsequent decrease likely reflects dendritic pruning processes (De Bellis et al 2001 ). Previous work in mice has shown that klotho plays a role in neurodevelopment, including myelination (Chen et al 2013 ), synaptic function (Dubal et al 2014 ) and dendritic arborization (Laszczyk et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%